Resilience among nurses working in maternity wards in Bangladesh: A qualitative study - Sharma, Aarav; Patel, Priya; Mehta, Rohan (STIKes Al-Ma'arif Baturaja, 2025)
Background: Nurses working in maternity wards in Bangladesh face complex clinical and emotional challenges due to maternal complications, high patient loads, and limited resources. Resilience has been recognized as a critical factor in helping nurses cope with stress, adapt to demanding environments, and sustain compassionate care. Objective: This study aimed to explore and describe the experiences of resilience among nurses working in maternity wards in Bangladesh. Methods: A qualitative interpretive descriptive design was employed, guided by Thorne’s framework. Purposive sampling recruited eight registered nurses from maternity units, including labor and delivery, postnatal, and maternal high-dependency wards, in tertiary hospitals. Semi-structured individual interviews were conducted between October 2020 and January 2021, lasting 30–90 minutes, and were audio recorded. Data were analyzed inductively to identify themes reflecting resilience experiences. Trustworthiness was ensured using COREQ guidelines. Results: Three overarching themes emerged: (1) The transition period, reflecting anxiety and lack of preparedness during the early stages of maternity nursing; (2) Gaining trust of mothers, families, and colleagues, highlighting the challenges of acceptance, communication, and professional recognition; and (3) Having a positive mindset, emphasizing psychological resilience, optimism, and self-care practices that enabled nurses to cope with workplace stress. Conclusion: Resilience among maternity nurses in Bangladesh is developed through a dynamic interplay of personal adaptation, social support, and psychological coping strategies. Strengthening structured mentorship, fostering supportive workplace cultures, and integrating resilience training into professional development are crucial to enhance maternal care quality and reduce burnout among maternity nurses.